The challenges and opportunities of creating an effective lesson at tertiary level - Elena Vasilievna Velikaya (Indonesian TESOL Journal, 2020)
Any teacher, beginner or experienced, wants to teach an effective and successful lesson. The notion of effective teaching is rather difficult: two teachers can teach the same lesson, but differently, and both lessons can be effective. This article deals with some principles which can make a lesson effective, such as lesson management, lesson structure, students’ motivation to study, and class size. This research into students’ attitude to class size covers four groups from academic year 2016-2017 (faculty of linguistics at the National Research University Higher School of Economics – NRU HSE), six groups from academic year 2017-2018 (faculty of linguistics), and four groups from academic year 2017-2018 (International College of Economics and Finance – ICEF). Students’ replies to the question of whether they like to study in large or small groups show that most students prefer to study in small groups; the standard number of students in a first-year class is 15, but in reality can exceed 20.